Santri and AI: Ethical Reflections on Islamic Learning Through Az-Zarnuji’s Ta'limul Muta'allim - Rahman, Fazlul; Mala, Faiqotul (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2025)
The rapid development of artificial intelligence (AI) has significantly transformed the education landscape, including within traditional Islamic institutions. This conceptual study examines the ethical implications of AI-based Islamic learning, particularly through the lens of Ta'limul Muta'allim, a classical pedagogical text by Az-Zarnuji widely revered in Pesantren traditions. Using a library research method, the study critically analyzes the principles of Islamic learning, such as the sanctity of the teacher-student relationship, the role of sincerity (ikhlas), and the etiquette of knowledge-seeking (adab)—in contrast to the mechanized, impersonal features of AI-driven education. The paper also reviews contemporary scholarly works on AI and its intersection with religious pedagogy. The findings reveal that while AI offers potential for accessibility and scalability in Islamic learning, it challenges spiritual integrity, traditional epistemology, and ethical values. The study concludes by proposing a normative framework for AI usage in Islamic education that remains faithful to the ethical spirit of Az-Zarnuji's teachings.